A time for decision - Adaza, Homobono A. (Homobono Adaza, 1986)
This book is designed to document the passing events. It is one man's view of the Cory Aquino presidency from February 25, 1986 to October 1986. The speeches in this volume are brief. They were delivered before composite audiences in the Philippines--from civic clubs to student groups and press and radio clubs. They are programmed to provoke thinking and analysis and elicit participatory reactions--Foreword.